HIGIENE, EUGENIA E SAÚDE PÚBLICA NA OBRA DE BELISÁRIO PENNA (1910-1920) - Oliveira, Jhallesson Kovaliki de (2020)
This dissertation deals with the discussions on hygiene, eugenics and public health in Brazil, in the beginning of the 20th century. Its objective is to analyze the performance of the medical-sanitary and intellectual Belisário Penna (1868-1939), in the Brazilian sanitary movement, of the 1910s. He was part of the generation of doctors and scientists of the beginning of the 20th century, who debate on the reform of Brazilian society, the construction of national identity and the political process that the nation should take to follow the longed-for path of civilization. In this research, we analyzed a set of documentary sources, produced by Penna, in the 1910s and 1920s, in particular, texts from newspapers and magazines, scientific travel reports and books published by the author, including Saneamento do Brasil, published in 1918 These sources express the involvement of the health worker in the medical, political and scientific debates of the time, around the process of reforming Brazilian society and national construction. Penna found, in medical science and hygienic conceptions, the necessary tools for the construction of a political project that aimed at the implantation of a wide engineering of public health reform and national regeneration. With the emergence of eugenics in Brazil, in the first decades of the twentieth century, he absorbed a softer eugenic prescription, in the style of “preventive” eugenics, incorporating these ideas into the sanitary movement he led. In this sense, the central interest of this research is to analyze how Penna approaches hygiene and eugenics in his discussions on social reform and public health policies, in Brazil, between the decades of 1910 to 1920. The research also analyzes, within the project Penna's national health system, his conception of hygienic education as a way to build what he called “national health awareness”. The methodology for the development of this dissertation is based on the history of intellectuals and is supported by the perspective of linguistic contextualism, proposed by historian Quentin Skinner. We also use the concept of biopolitics, by Michel Foucault, which represents the exercise of the power of modernity, haracterized by the encouragement, reinforcement, control and surveillance managed over people's lives.